Economic Efficiency of Investing in Construction - Gaybullaevna, Rasulova Sharifa (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article discusses the role of the building materials industry in the economy of Uzbekistan, long-term plans for the impact of corporate governance on the target direction of building materials. The current state of the construction industry is summarized, the structure of investments in fixed capital is analyzed. Using the macroeconomic multiplier, the contribution of construction to the development of other sectors of the economy of Uzbekistan was studied.